2002
DOI: 10.1002/chin.200214218
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Daphnicyclidins A—H, Novel Hexa‐ or Pentacyclic Alkaloids from Two Species of Daphniphyllum.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…In addition to some assignments based on chemical correlations and structural similarity arguments, 33,71 a safe configurational assignment had been reported for daphnicyclidin F (5, Chart 2), a compound related to macropodumine C. It was based on the exciton chirality approach, and involved the synthesis of the p-bromobenzoate derivative (5a) and the analysis of its CD spectrum dominated by the exciton coupling between the benzoate and the substituted fulvene chromophore. 72 The CD spectra of other daphnicyclidins (6)(7)(8) and of a related daphnipaxinin (9) had also been reported and employed for configurational assignment. 72,73 The procedure followed in these latter cases lays, however, on a less clear-cut exciton chirality analysis, because the diene and the C¼ ¼O double bonds in 5-9 were incorrectly considered as independent units and their exciton coupling discussed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to some assignments based on chemical correlations and structural similarity arguments, 33,71 a safe configurational assignment had been reported for daphnicyclidin F (5, Chart 2), a compound related to macropodumine C. It was based on the exciton chirality approach, and involved the synthesis of the p-bromobenzoate derivative (5a) and the analysis of its CD spectrum dominated by the exciton coupling between the benzoate and the substituted fulvene chromophore. 72 The CD spectra of other daphnicyclidins (6)(7)(8) and of a related daphnipaxinin (9) had also been reported and employed for configurational assignment. 72,73 The procedure followed in these latter cases lays, however, on a less clear-cut exciton chirality analysis, because the diene and the C¼ ¼O double bonds in 5-9 were incorrectly considered as independent units and their exciton coupling discussed.…”
Section: Discussionmentioning
confidence: 96%
“…72 The CD spectra of other daphnicyclidins (6)(7)(8) and of a related daphnipaxinin (9) had also been reported and employed for configurational assignment. 72,73 The procedure followed in these latter cases lays, however, on a less clear-cut exciton chirality analysis, because the diene and the C¼ ¼O double bonds in 5-9 were incorrectly considered as independent units and their exciton coupling discussed. A prerequisite of the exciton chirality method is however that the two or more interacting units have negligible molecular overlap, such that conjugation, electron exchange, and resonance phenomena may be excluded.…”
Section: Discussionmentioning
confidence: 96%
“…We undertook a systematic analysis of the biogenesis of selected Daphniphyllum alkaloids (1-14, Figures 1A-1D) from the macrodaphniphyllamine, calyciphylline A, daphnilongeranin A, and daphnicyclidin D subfamilies [30][31][32][33][34][35][36][37][38][39][40] , on the basis of their structural relationships and biosynthetic hypotheses. The biosynthetic network of these alkaloids is outlined in Figure 1E.…”
Section: An Envisioned Chemically Synthetic Network Of Selected Daphn...mentioning
confidence: 99%
“…In 2001, Kobayashi et al 17 reported the isolation of daphnicyclidins A−H from the stems of Daphniphyllum humile and D. teijsmanni. Their structures and stereochemistry were determined on the basis of spectroscopic data and by chemical means and were further confirmed by X-ray crystallography.…”
Section: Synthesis Of Daphnicyclidin A-type Alkaloidsmentioning
confidence: 99%
“…Daphnicyclidin A-type alkaloids possess fused hexa-or pentacyclic structures harboring five stereogenic centers (Figure 9). 17,116 According to the biosynthetic proposal by Kobayashi et al, 17 Tosylation, followed by treatment with TBAF, gave the exocyclic enone via an S N 2′ displacement mode, which upon hydrogenation with Pd-on-carbon gave 206 as an equal mixture of diastereomers. Upon treatment with AcCl in i PrOH, ketone 206 underwent acetal cleavage, followed by iminium ion formation and subsequent Mannich-type addition, to give a separable mixture of 207 and 208.…”
Section: Synthesis Of Daphnicyclidin A-type Alkaloidsmentioning
confidence: 99%